2021
DOI: 10.1111/1440-1681.13597
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new pharmacokinetic model for target‐concentration controlled infusion of vancomycin in critically ill patients

Abstract: The aim of this prospective study was to construct a new pharmacokinetic model of vancomycin for target-concentration controlled infusion (TCI). As the first loading dose, 25 mg/kg of vancomycin was administered during 60-90 min. Arterial blood samples were obtained at pre-set intervals to measure the serum concentrations of vancomycin. Population pharmacokinetic analysis was performed using the NONMEM software (ICON Development Solutions). In total, 197 serum concentration measurements from 22 patients were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…Vancomycin clearance was increased with BW in the final model, which was consistent with the results in the literature ( Mangin et al, 2014 ; Jing et al, 2020 ; Lin et al, 2021 ; Wang et al, 2021 ; Bang et al, 2022 ). The influence of BW on CL is related to various physiological changes, including increased renal mass and cardiac output, both of which could increase renal blood flow, and ultimately increased vancomycin CL ( Grace, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Vancomycin clearance was increased with BW in the final model, which was consistent with the results in the literature ( Mangin et al, 2014 ; Jing et al, 2020 ; Lin et al, 2021 ; Wang et al, 2021 ; Bang et al, 2022 ). The influence of BW on CL is related to various physiological changes, including increased renal mass and cardiac output, both of which could increase renal blood flow, and ultimately increased vancomycin CL ( Grace, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that renal function and body weight (BW) were the most important influencing factors for vancomycin clearance (CL) and apparent volume of distribution (V), respectively, and both two factors should be considered for its dose adjustment ( Lin et al, 2021 ; Revilla et al, 2010 ; Medellín-Garibay et al, 2017 ; Mangin et al, 2014 ; Llopis-Salvia and Jiménez-Torres, 2006 ; Jalusic et al, 2021 ; Yang et al, 2017 ; Huang et al, 2021 ; del Mar Fernández de Gatta Garcia et al, 2007 ; CHEN et al, 2013 ; Marsot et al, 2012 ; Colin et al, 2019 ). Furthermore, sex, age, serum albumin levels, disease status, concomitant drugs (e.g., meropenem and dopamine), and mechanical support (e.g., renal replacement therapy (RRT) and mechanical ventilation) could also affect vancomycin pharmacokinetics ( Lin et al, 2021 ; Revilla et al, 2010 ; Medellín-Garibay et al, 2017 ; Mangin et al, 2014 ; Jalusic et al, 2021 ; Yang et al, 2017 ; del Mar Fernández de Gatta Garcia et al, 2007 ; Yang et al, 2018 ; Bang et al, 2022 ; ZENG et al, 2016 ; Alqahtani et al, 2018 ; Economou et al, 2018 ; Garreau et al, 2021 ; Jing et al, 2020 ; Kanji et al, 2020 ; Wang et al, 2021 ; Kim et al, 2016 ; Li et al, 2017 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not intend to carry out a rigorous external validation, this is the preliminary validation to determine whether there is an adequate implementation of the models and to be able to move toward an adaptation process through the continuous learning approach. It is assumed that, in clinical practice, the challenge is to create a targetconcentration-controlled infusion (TCI) strategy, as an infusion method for personalized patient dosing in critically ill patients; however, the PK model must undergo adequate external validation [41]. Commonly available Bayesian pharmacokinetic models lack precision in the critically ill; until this precision is improved, AUC24 calculation using two concentrations via kinetic equations or continuous vancomycin infusion with a single concentration at steady state may be preferable in this population [42].…”
Section: Discussionmentioning
confidence: 99%